Prinsip Hukum Fiqih Muamalah dalam Transaksi Ekonomi Kontemporer : Analisis Normatif dan Aplikatif - Rudi Hartono I; Abdul Ikrom; Annisa Mardhatillah; Meizatul Hasanah; Muhammad Dzikrullah (Jurnal Budi Pekerti Agama Islam, 2025)
This scientific article comprehensively investigates the fundamental principles of Fiqh Muamalah governing Islamic economic transactions, focusing on three primary areas: sale (bay'), debt-financing (dayn), and leasing (ijarah). This research aims to analyze the Sharia conceptual framework underlying each contract, including its pillars, conditions, and legal implications, as well as to identify crucial prohibitions such as gharar (ambiguity), riba (interest/unlawful increment), and maysir (speculation). Furthermore, this article explores the relevance and challenges of applying these principles within the dynamic context of the modern economy, characterized by financial innovation, digital technology, and globalization. Through an in-depth literature study and a comparative analysis of classical and contemporary scholars' interpretations, this research examines how ethical Islamic principles such as justice ('adl), mutual consent (taradhi), and public interest (maslahah) can be integrated into current business practices. Selected case studies on e-commerce transactions, digital lending platforms, and technology-based leasing models are analyzed to illustrate the challenges and potential solutions in applying Fiqh Muamalah. This article concludes by offering a perspective on the importance of contextual reinterpretation and the innovation of Islamic financial products to ensure the relevance of Fiqh Muamalah in addressing global economic challenges while upholding Islamic values.